Unpacking Partnership, Engagement, and Collaboration Research to Inform Implementation Strategies Development: Theoretical Frameworks and Emerging Methodologies - Huang, Keng-Yen; Kwon, Simona C.; Cheng, Sabrina; Kamboukos, Dimitra; Shelley, Donna; Brotman, Laurie M.; Kaplan, Sue A.; Olugbenga, Ogedegbe; Hoagwood, Kimberly (Frontiers in Public Health, 2018)
Background: Partnership, engagement, and collaboration (PEC) are critical factors in dissemination and implementation (D&I) research. Despite a growing recognition that incorporating PEC strategies in D&I research is likely to increase the relevance, feasibility, impacts, and of evidence-based interventions or practices (EBIs, EBPs), conceptual frameworks and methodologies to guide the development and testing of PEC strategies in D&I research are lacking. To address this methodological gap, a review was conducted to summarize what we know, what we think we know, and what we need to know about PEC to inform D&I research. Methods: A cross-field scoping review, drawing upon a broad range of PEC related literature in health, was conducted. Publications reviewed focused on factors influencing PEC, and processes, mechanisms and strategies for promoting effective PEC. The review was conducted separately for three forms of partnerships that are commonly used in D&I research: (1) consumer-provider or patient-implementer partnership; (2) delivery system or implementation team partnership; and (3) sustainment/support or interagency/community partnership. A total of 39 studies, of which 21 were review articles, were selected for an in-depth review. Results: Across three forms of partnerships, four domains (cognitive, interpersonal/affective, behavioral, and contextual domains) were consistently identified as factors and strategies for promoting PEC. Depending on the stage (preparation or execution) and purpose of the partnership (regulating performance or managing maintenance), certain PEC strategies are more or less relevant. Recent developments of PEC frameworks, such as Partnership Stage of Change and multiple dynamic processes, provide more comprehensive conceptual explanations for PEC mechanisms, which can better guide PEC strategies selection and integration in D&I research. Conclusions: This review contributes to D&I knowledge by identifying critical domain factors, processes, or mechanisms, and key strategies for PEC, and offers a multi-level PEC framework for future research to build the evidence base. However, more research is needed to test PEC mechanisms.